Von Willebrand Factor Gene Variants Associate with Herpes simplex Encephalitis - Abdelmagid, Nada; Bereczky-Veress, Biborka; Atanur, Santosh; Musilová, Alena; Zídek, Václav; Saba, Laura; Warnecke, Andreas; Khademi, Mohsen; Studahl, Marie; Aurelius, Elisabeth; Hjalmarsson, Anders; Garcia-Diaz, Ana; et al. (PloS one, 2016)
Herpes simplex encephalitis (HSE) is a rare complication of Herpes simplex virus type-1 infection. It results in severe parenchymal damage in the brain. Although viral latency in neurons is very common in the population, it remains unclear why certain individuals develop HSE. Here we explore potential host genetic variants predisposing to HSE. In order to investigate this we used a rat HSE model comparing the HSE susceptible SHR (Spontaneously Hypertensive Rats) with the asymptomatic infection of BN (Brown Norway). Notably, both strains have HSV-1 spread to the CNS at four days after infection. A genome wide linkage analysis of 29 infected HXB/BXH RILs (recombinant inbred lines-generated from the prior two strains), displayed variable susceptibility to HSE enabling the definition of a significant QTL (quantitative trait locus) named Hse6 towards the end of chromosome 4 (160.89-174Mb) containing the Vwf (von Willebrand factor) gene. This was the only gene in the QTL with both cis-regulation in the brain and included several non-synonymous SNPs (single nucleotide polymorphism). Intriguingly, in human chromosome 12 several SNPs within the intronic region between exon 43 and 44 of the VWF gene were associated with human HSE pathogenesis. In particular, rs917859 is nominally associated with an odds ratio of 1.5 (95% CI 1.11-2.02; p-value = 0.008) after genotyping in 115 HSE cases and 428 controls. Although there are possibly several genetic and environmental factors involved in development of HSE, our study identifies variants of the VWF gene as candidates for susceptibility in experimental and human HSE.
Keywords: von Willebrandův faktor; Animals; Quantitative Trait, Heritable; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; herpetická encefalitida; kvantitativní znak dědičný; Chromosomes, Mammalian; Encephalitis, Herpes Simplex; Genotyping Techniques; genotypizační techniky; krysa rodu Rattus; potkani inbrední SHR; von Willebrand Factor; zvířata; savčí chromozomy; lidský herpesvirus 1; Rats; Rats, Inbred SHR; Herpesvirus 1, Human; Humans